The interdisciplinary nature of technology education: a means of promoting 'hands-on' and 'minds-on' activities - De Swart, Estelle; Ankiewicz, Piet (University of the Free State, 2000)
Because the interdisciplinary nature of technology education facilitates its integration with other school subjects, the first aim of this study was to explore and illustrate the possible link between information technology (typewriting) and technology education. Secondly, the study attempted to determine learners' experiences in respect of the development of thinking skills by means of an interdisciplinary approach. This project was developed within a qualitative paradigm and with fourteen grade 10 pupils. It was evident that a link between the two abovementioned fields can be successfully established and that education can promote the type of meaningful learning which empowers learners to be independent, courageous and responsible in taking decisions. Purposeful learning opportunities must therefore be created in order to enable learners to participate in 'minds-on' activities.

Vanweë die interdissiplinere aard van tegnologie-onderwys wat die integrasie met ander skoolvakke moontlik maak, was die doel om eerstens die moontlike koppeling tussen inligtingstegnologie (tik) en tegnologie-onderwys te verken en te illustreer. Die tweede doel was om die persepsies van leerders ten aansien van die ontwikkeling van denkvaardighede in so 'n interdissiplinêre benadering te bepaal. Die projek is binne die kwalitatiewe paradigma, onder veertien graad 10 leerders gedoen. Dit kan afgelei word dat 'n koppeling russen die twee velde suksesvol gedoen kan word en dat onderwys wat leerders bemagtig om onafhanklike, waagmoedige en verantwoordelike besluice ce kan neem, bevorder behoort te word. Doelgerigte geleenthede vir leerervarings, waar leerders deel kan hê aan 'minds-on' aktiwiteite, moet bewerkstellig word.